A Perspective Of Marine Mining Within De Beers - K. Richardson (The Southern African Institute of Mining and Metallurgy, 2007)
Although the De Beers group has a long history of placer mining on land, the group only became actively involved in deep water marine diamond exploration and mining in 1983 with the formation of DeBeers Marine. Full-scale commercial mining commenced around1991. Since then, the group marine mining capability has grown into a formidable fleet of 8 large deep water (>70 m) mining vessels, as well as other special purpose geosurvey platforms. Marine diamond production by the group is expected to be just short of 1 million carats in 2006. De Beers operates across the entire value-chain spectrum from geology and geosurvey, through sampling to mining, and finally ore processing into high value concentrate. Supporting these operations involves significant service activities such as maintenance, security, logistics and environmental management. Specific challenges exist in terms of developing or acquiring appropriate technology for marine mining. These challenges have resulted in De Beers operating extensive in-house R&D and projects departments, as well as drawing extensively from technology partners. An array of computational and test facilities is also available to support R&D and projects activities. Hydrotransport in various guises is key to the current approaches to marine mining and ore processing. Use is made of airlift and centrifugal pumping for hydraulic hoisting of very coarse gravel, while splitters, launders, dewatering, elutriators, jet pumps, centrifugal pumps, dense medium circuits, pipeline systems, and instrumentation for coarse abrasive particles are used extensively in the ore processing plant.